EXPLORING THE LEGAL MULTICULTURALISM WITHIN THE THARIQOH QODIRIYYAH WA NAQSYABANDIYYAH: A CASE STUDY OF DARUL FALAH COMMUNITY IN PAGUTAN MATARAM - Bakri; Mutawalli; Ahmad Muhassim; Zulkarnain (AS-SALAM, 2023)
The study of legal multiculturalism is a very important topic to be researched because it is related to its significant influence on the diversity of cultures, religions, and traditions in society. This research aims to identify the forms, and dimensions of legal multiculturalism in Thariqoh Qodiriyah wa Naqsyabandiyah Darul Falah and the practice of family law for its adherents. The method used in the research is a qualitative method with data collection through documentation and interviews. The results of the study found that; (1) the form of legal multiculturalism in Thariqoh Qodiriah wa Naqsyabandiyah is seen from the acceptance of four Mazhabs as the basis for implementing laws related to furu' issues, religious and cultural tolerance, social services without discrimination, respect for cultural values, contribution to peace and social welfare with a very strong dimension of Tasawwuf through self-purification, (2) the practice of family law values for adherents includes; the implementation of walimah when getting married, practicing praiseworthy behavior and pleasing the family, providing for the family properly, and deciding something important through istikharah or Mursyid’s permission such as divorce and others. The findings are expected to illustrate the way in which spiritual teachings and practices can coexist with the challenges of contemporary life, including cultural and religious diversity.